2019
DOI: 10.3390/nu11081820
|View full text |Cite
|
Sign up to set email alerts
|

The Aryl Hydrocarbon Receptor (AhR) Mediates the Counter-Regulatory Effects of Pelargonidins in Models of Inflammation and Metabolic Dysfunctions

Abstract: Pelargonidins are anthocyanidins thought to be beneficial for the human health, although controversies exist over the doses needed and the unclear mechanism of action, along with poor systemic bioavailability. One putative target of pelargonidins is the aryl hydrocarbon receptor (AhR). A synthetic pelargonidin (Mt-P) was synthesized by the methylation of the pelargonidin (the natural compound indicated as P). Mt-P transactivated the AhR with an EC50 of 1.97 µM and was ~2-fold more potent than the natural compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…The impact of polyphenols containing plant extracts [ 42 , 43 , 63 , 64 ] or pure phenolic compounds [ 65 , 66 ] on TNF- α and IL-17 colonic levels was studied by some other research studies. Furthermore, it is noteworthy that in TNBS-subjected rats, one of the polyphenol groups, anthocyanins, especially pelargonidin, not only reversed intestinal inflammation and increased expression of TNF- α and IL-6 but also promoted the anti-inflammatory M2 macrophage expansion, which is inhibited by chemerin [ 67 ]. We did not find any previous studies investigating the impact of polyphenolic compounds, including cornelian cherry extract on chemerin tissue levels during TNBS colitis.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of polyphenols containing plant extracts [ 42 , 43 , 63 , 64 ] or pure phenolic compounds [ 65 , 66 ] on TNF- α and IL-17 colonic levels was studied by some other research studies. Furthermore, it is noteworthy that in TNBS-subjected rats, one of the polyphenol groups, anthocyanins, especially pelargonidin, not only reversed intestinal inflammation and increased expression of TNF- α and IL-6 but also promoted the anti-inflammatory M2 macrophage expansion, which is inhibited by chemerin [ 67 ]. We did not find any previous studies investigating the impact of polyphenolic compounds, including cornelian cherry extract on chemerin tissue levels during TNBS colitis.…”
Section: Discussionmentioning
confidence: 99%
“…While, similarly to other anthocyanins, pelargonidin is thought to be beneficial for human health [2325], controversies exist over the doses needed to reach these effects, along with poor systemic bioavailability and unclear mechanism(s) of action. In a previous study we have shown that the natural pelargonidin function as AhR ligand in vitro and attenuates intestinal inflammation in AhR-dependent manner [26]. In the present study we have investigated the potential of the natural pelargonidin in regulating ACE2 expression in colon in models of intestinal inflammation caused by exposure of wild type and AhR −/− mice to a high caloric intake and intestinal irritants.…”
Section: Introductionmentioning
confidence: 88%
“…In a previous study we have shown that the natural pelargonidin function as AhR ligand in vitro and attenuates intestinal inflammation in AhR-dependent manner [26]. In the present study we have investigated the potential of the natural pelargonidin in regulating ACE2 expression in colon in models of intestinal inflammation caused by exposure of wild type and AhR -/mice to a high caloric intake and intestinal irritants.…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, AhR is targeted by pelargonidins, a type of anthocyanidins thought to be beneficial for overall human health. A synthetic pelargonidin (Mt-P) transactivates AhR, and has been shown, in HFD-fed C57BL/6J mice, to attenuate body weight gain, intestinal and liver inflammation, and ameliorate insulin sensitivity, while worsening liver steatosis, of which were abrogated by gene ablation of AhR ( 232 ). Another study in DSS-colitis rats explored the effects of the anthocyanin, pelargonidin 3-glucoside (P3G), on IBD and metabolic syndrome.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%